Protreptikos, czyli zachęta do myślenia na XXI wiek - Szulakiewicz, Marek (Humaniora. Czasopismo Internetowe, 2022)
In ancient times, protreptics encouraged to something and directed the attention towards a goal. Their aim was often to change behaviour. Using this ancient form, the article is an incentive to restore thinking’s primary function in culture. The key threats, which have appeared in the culture of technology, have been presented. Increasingly, it is believed (also at universities) that a human being only needs information, preparation for the market, and he needs neither the meaning nor understanding of the information, nor the philosophical reflection. Thinking itself – following the example of John Dewey – is only associated with an increase in productivity. However, without concern for thinking and restoring its sapiential dimension, culture is threatened by infantilism and the loss of the meaning of our existence.